Thin Coated Adsorbent For The Removal Of Contaminant Of Emerging Concern - Shamsudin, Muhamad Sharafee (2020)
In Malaysia, issues of Contaminant of Emerging Concern (CEC) have been recently highlighted. Sulfamethoxazole and Acetaminophen were targeted pollutant in this research. There are a large amount of these pollutants have been detected in sewage treatment plants in Malaysia. Unfortunately, sewage treatment plants are not effective enough to overcome these pollutant. Therefore, in this research study, a new approach applying adsorption concept is introduced. A screened of potential adsorbents have done to select the suitable adsorbent to be introduced into coated adsorbent (COATER). Activated carbon was chosen as potential adsorbent. Contaminant Emerging Remover (COATER) for adsorption of sulfamethoxazole (SMX) and acetaminophen (ACT) were investigated. The COATER is formulated using Epoxidized Neutral Rubber (ENR-50) and poly(vinyl) chloride (PVC) as binders with activated carbon as an adsorbent, then was coated on white cotton fabric (substrate) via brushing technique. 4 g of activated carbon added into COATER (optimum weight of this study). Characterization analysis using SEM-EDX, FTIR and BET were performed. The results of surface morphology analysis showed good distributed of activated carbon and clearly attached adsorbent onto the substrate. Through elements analysis (EDX, nitrogen element detected attached on COATER adsorption which represents SMX and ACT. FTIR analysis detected amide formation occurred between COATER and SMX. The surface area and pore volume of the COATER were 64.3 m2/g and 0.07 cm3/g respectively. The COATER was evaluated through varies parameters including initial concentrations, temperatures, mixing rate and pH of solution. The adsorption capacity increased with increasing initial concentration. The optimum temperature of this adsorption process was 30℃. The optimum pH condition for SMX and ACT at actual pH (pH 4.80 for SMX) and (pH 6.05 for ACT), which gave the highest removal, 84.4% and 45%, respectively. The result of equilibrium and kinetic studies indicated that Langmuir isotherm model and pseudo-second-order, respectively, are best-fitted with the adsorption of SMX and ACT onto COATER. The thermodynamic studies indicacted that SMX and ACT were favor to exothermic process. However, for both adsorbates the process were favorable and spontaneous due to the